A cell-like structure reaction glaze and preparation method thereof

By designing cell-like structure reaction glaze, using the optimal fusion of base glaze and surface glaze and microcrystalline nucleus distribution, the problems of unstable quality and insufficient decorative properties of traditional glaze surfaces are solved, and the stable reaction effect and good decorative properties of glaze surfaces are achieved.

CN119774882APending Publication Date: 2025-04-08LINYI HONGSHUN PORCELAIN IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411991683.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional glaze surfaces are easily affected in many aspects during the preparation process, resulting in unstable product quality, blurred glaze surface reaction effect, and insufficient decorative properties.

Method used

The design of cell-like structure reaction glaze is adopted, through the optimal fusion of the base glaze and the uniformly distributed microcrystalline nucleus, a crystal of uniform size is formed, similar to the microstructure of animal cells, and the rich reaction effect of the glaze surface is achieved.

Benefits of technology

It achieves stable reaction effect and good decorative properties of the glaze surface, suitable for mass production, soft and rich glaze surface, and consistent reaction effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774882A_ABST
    Figure CN119774882A_ABST
Patent Text Reader

Abstract

The invention relates to the field of reaction glaze and a preparation method thereof, in particular to a cell-like structure reaction glaze and a preparation method thereof, comprising: base glaze: 21 to 23 parts of frit, 27 to 29 parts of potassium feldspar powder, 14 to 16 parts of microcrystalline stone, 13 to 16 parts of wollastonite powder, 1 to 3 parts of calcined talc powder, 4 to 6 parts of molecular sieve, 3 to 5 parts of zinc oxide, 2 to 4 parts of Guizhou soil, and 6 to 8 parts of 350 glaze powder; top glaze: 21 to 23 parts of frit, 27 to 29 parts of potassium feldspar powder, 14 to 16 parts of microcrystalline stone, 13 to 16 parts of wollastonite powder, 1 to 3 parts of calcined talc powder, 4 to 6 parts of molecular sieve, 3 to 5 parts of zinc oxide, 2 to 4 parts of Guizhou soil, and 6 to 8 parts of 350 glaze powder; 27 to 29 parts of stone powder, 14 to 16 parts of microcrystalline stone, 13 to 16 parts of wollastonite powder, 1 to 3 parts of calcined talc, 4 to 6 parts of molecular sieve, 3 to 5 parts of zinc oxide, 2 to 4 parts of Guizhou soil, 6 to 8 parts of 350 glaze powder, and 3 to 8 parts of colorant; the cell-like structure reaction glaze of the present invention mainly utilizes the optimal fusion of base glaze and surface glaze, and the evenly distributed microcrystalline nuclei grow simultaneously to form crystals of uniform size, forming an extremely imaginative reaction effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of reaction glazes and preparation methods thereof, and in particular to a cell-like structure reaction glaze and a preparation method thereof. Background Art

[0002] As one of the birthplaces of ceramics, Luozhuang area has rich and colorful products, most of which are general porcelain products, including ordinary white porcelain, high-temperature colored glaze products, kiln-changed glaze, reaction glaze products, etc. The kiln-changed glaze and reaction glaze products have just entered the market in the field of high-temperature white porcelain products and have been warmly sought after and liked by the market.

[0003] Traditional glazes are usually made of raw materials such as feldspar, quartz, and clay. During preparation, these raw materials are mixed in a certain proportion and adjusted with an appropriate amount of water to form a glaze slurry. The prepared glaze slurry is evenly applied to the surface of the porcelain. The glazed porcelain is sent to the kiln for high-temperature firing. After firing, the porcelain needs to be cooled to room temperature. The above-mentioned glaze preparation method will form a relatively thin layer of glaze covering the ceramic substrate. However, during the preparation and firing process of the glaze, due to the influence of various factors, such as glaze formula, glazing process, firing temperature and time, etc., various defects may occur on the glaze, and the product quality stability is insufficient when leaving the factory. At the same time, the glaze reaction effect is vague and the decorative effect is insufficient.

[0004] Therefore, in order to address the problems that the above-mentioned traditional glaze is easily affected by many factors during the preparation process, is prone to defective products, and has a vague glaze reaction effect and insufficient decorativeness, a cell-like structure reaction glaze and its preparation method can be designed. Summary of the invention

[0005] In order to overcome the problems that traditional glazes are easily affected by many factors during the preparation process, defective products are easily produced, and the glaze reaction effect is vague and the decorative effect is insufficient.

[0006] The technical solution of the present invention is: a cell-like structure reaction glaze, comprising the following raw materials in parts by weight:

[0007] Base glaze: 21-23 parts of frit, 27-29 parts of potassium feldspar powder, 14-16 parts of microcrystalline stone, 13-16 parts of wollastonite powder, 1-3 parts of calcined talc, 4-6 parts of molecular sieve, 3-5 parts of zinc oxide, 2-4 parts of Guizhou soil, 6-8 parts of 350 glaze powder;

[0008] Top glaze: 21 to 23 parts of frit, 27 to 29 parts of potassium feldspar powder, 14 to 16 parts of microcrystalline stone, 13 to 16 parts of wollastonite powder, 1 to 3 parts of calcined talc, 4 to 6 parts of molecular sieve, 3 to 5 parts of zinc oxide, 2 to 4 parts of Guizhou soil, 6 to 8 parts of 350 glaze powder, and 3 to 8 parts of colorant.

[0009] Preferably, the raw materials are as follows in parts by weight:

[0010] Base glaze: 22 parts of frit, 27 parts of potassium feldspar powder, 15 parts of microcrystalline stone, 14 parts of wollastonite powder, 2 parts of calcined talc powder, 4 parts of molecular sieve, 3 parts of zinc oxide, 3 parts of Guizhou soil, 7 parts of 350 glaze powder;

[0011] Top glaze: 22 parts of frit, 27 parts of potassium feldspar powder, 15 parts of microcrystalline stone, 14 parts of wollastonite powder, 2 parts of calcined talc, 4 parts of molecular sieve, 3 parts of zinc oxide, 3 parts of Guizhou soil, 7 parts of 350 glaze powder, 5 parts of colorant, and 0.5 parts of high cobalt black.

[0012] Preferably, the colorant is ordinary light red tea colorant for ceramics.

[0013] A cell-like structure reaction glaze and a preparation method thereof, comprising the cell-like structure reaction glaze described above, and the steps are as follows:

[0014] Step 1: Mix the base glaze and top glaze raw materials according to the weight ratio and add appropriate amount of water;

[0015] Step 2: wet ball milling, sieving, adjusting to a suitable concentration to obtain glaze slurry. The requirements for the fineness of the glaze slurry for the bottom glaze and the top glaze are: the sieve residue after passing through a 325-mesh screen is 0.1% to 0.2%, and the glaze slurry concentration is 46 to 50 degrees Baume. The ball milling method is: the components in the formula are weighed according to the percentage of the mixed dry material, ball stone and water in a weight ratio of 1:2:0.5, and put into a ball mill for ball milling. The ball milling time is determined according to the weight of the material stone water and the required fineness. After the glaze slurry is out of the ball, it is sieved through a 160-mesh screen and iron is removed with an iron removal rod. It is adjusted to a suitable concentration with water or electrolyte;

[0016] Step three: Then use the dipping method to attach the base glaze to the bisque-fired blank. The bisque-fired temperature is 780℃~850℃. After the blank is immersed in the base glaze, it is sent to the oven for drying at a temperature of 55℃~70℃. After the base glaze is dried, take it out and use the spraying method to evenly attach the surface glaze to the base glaze. The concentration of the surface glaze is controlled at 53~60 degrees Baume. After drying again, it is sent to the tunnel kiln for firing. The maximum temperature is 1260℃~1290℃, the firing cycle is 13h~15h, and the firing atmosphere is an oxidizing atmosphere.

[0017] Preferably, the concentration of the base glaze slurry is controlled at 38 to 44 degrees Baume.

[0018] Preferably, the concentration of the top glaze slurry is controlled at 53 to 60 degrees Baume.

[0019] Preferably, the glaze slurry is passed through a 160-mesh sieve after being spherical and iron is removed using an iron removal rod.

[0020] Preferably, the base glaze is attached to the blank by dipping method; and the surface glaze is evenly attached to the base glaze by spraying method.

[0021] Beneficial effects of the present invention:

[0022] The glaze reaction effect of the present invention is different from that of other reaction glazes. It is a highly innovative reaction glaze with good decorative effect, soft and rich glaze surface, stable reaction effect, and suitable for mass production. The cell-like structure reaction glaze of the present invention mainly utilizes the best fusion of the base glaze and the surface glaze, and the uniformly distributed microcrystalline nuclei grow simultaneously to form crystals of uniform size, which are similar to the microscopic structure of animal cells, forming a highly imaginative reaction effect.

[0023] The present invention is a cell-like structure reaction glaze. By introducing a certain amount of flux and alkaline earth metals, the base glaze and the surface glaze are creatively used with the same formula and different production processes. During the firing process, the base glaze and the surface glaze melt at the same time, but the surface glaze has a slightly lower melting point temperature than the base glaze due to the addition of colorants. When the surface glaze melts, it blends with the base glaze. There is no obvious relative flow between the base glaze and the surface glaze. The reaction is carried out evenly on the entire glaze surface. The glaze layer continues to react in the high-temperature zone, and the reaction effect continues to intensify. As the temperature changes, it enters the cooling stage, the glaze layer begins to condense and solidify, crystal nuclei appear evenly on the entire glaze surface, and crystals grow evenly. The glaze layer stops reacting, and the reaction effect solidifies as the glaze layer condenses. The cell-like structure reaction glaze glaze effect of the present invention is produced after leaving the kiln;

[0024] The present invention mainly introduces low-temperature frits, uses mixed fluxes such as microcrystalline stone and molecular sieve produced in Liling, Hunan, stabilizes the flowability of the glaze layer, and adjusts the initial melting point temperature of the bottom glaze and the top glaze by controlling the flux content, so that the top glaze and the bottom glaze are relatively immobile during the firing process, and promotes the uniform formation of crystal nuclei. In addition, 350 glaze powder is introduced to adjust the expansion coefficient and stability of the glaze to ensure the performance of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Shown is a schematic diagram of a firing curve of the reaction glaze and a preparation method thereof of the present invention;

[0026] Figure 2 The glaze effect diagram of Example 1 of the reaction glaze and preparation method thereof of the present invention is shown;

[0027] Figure 3 The glaze effect diagram of Example 2 of the reaction glaze and preparation method thereof of the present invention is shown;

[0028] Figure 4 The glaze effect diagram of Example 3 of the reaction glaze and preparation method thereof of the present invention is shown;

[0029] Figure 5 Shown is the glaze effect diagram of comparative example 1 of the reaction glaze and preparation method thereof of the present invention. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with the embodiments.

[0031] Example 1

[0032] The present invention provides an embodiment: a cell-like structure reaction glaze, comprising the following raw materials in parts by weight:

[0033] Base glaze: 20 parts of frit, 30 parts of potassium feldspar powder, 14 parts of microcrystalline stone, 12 parts of wollastonite powder, 2 parts of calcined talc, 9 parts of molecular sieve, 3 parts of zinc oxide, 3 parts of Guizhou soil, 7 parts of 350 glaze powder;

[0034] Top glaze: 24 parts of frit, 30 parts of potassium feldspar powder, 13 parts of microcrystalline stone, 12 parts of wollastonite powder, 2 parts of calcined talc, 7 parts of molecular sieve, 4 parts of zinc oxide, 2 parts of Guizhou soil, 6 parts of 350 glaze powder, and 5 parts of colorant.

[0035] Preparation method: Step 1, add them to the ball mill respectively, add appropriate amount of water, and ball mill together. The mass ratio of raw materials, ball stone, and water is 1:2:0.5, and the mass ratio of large ball stone, medium ball stone, and small ball stone in high-aluminum ball stone is 2:5.5:2.5. The ball milling time is 18 hours. After the glaze is out of the ball, it is passed through a 120-mesh screen to obtain a glaze slurry;

[0036] Step 2: add water to the base glaze to adjust to 40 degrees Baume, add water to the top glaze to adjust to 56 degrees Baume, use the dipping method to attach the base glaze slurry to the body, dry at 55℃~70℃ for 1h~1.5h, after drying, use the spraying method to evenly attach the top glaze to the base glaze, dry for 0.5 hours, send the glaze body into the tunnel kiln for firing, the firing cycle is 750min, the highest actual temperature of the kiln is 1280℃, and the firing curve is as follows: Figure 1 As shown, the firing atmosphere is an oxidizing atmosphere.

[0037] The final glaze effect of the product is as follows Figure 2 shown.

[0038] A reaction glaze prepared by a preparation method of a cell-like structure reaction glaze is provided in Example 1, and its glaze surface has rich reaction effects, good glossiness, and various physical and chemical properties meet relevant national standards, but a large number of glaze bubbles appear on its glaze surface, and they are more obvious in places where the glaze layer is slightly thicker.

[0039] Example 2

[0040] The present invention provides an embodiment: a cell-like structure reaction glaze, comprising the following raw materials in parts by weight:

[0041] Base glaze: 22 parts of frit, 27 parts of potassium feldspar powder, 15 parts of microcrystalline stone, 14 parts of wollastonite powder, 2 parts of calcined talc powder, 4 parts of molecular sieve, 3 parts of zinc oxide, 3 parts of Guizhou soil, 7 parts of 350 glaze powder;

[0042] Top glaze: 22 parts of frit, 27 parts of potassium feldspar powder, 15 parts of microcrystalline stone, 14 parts of wollastonite powder, 2 parts of calcined talc, 4 parts of molecular sieve, 3 parts of zinc oxide, 3 parts of Guizhou soil, 7 parts of 350 glaze powder, 5 parts of colorant, and 0.5 parts of high cobalt black.

[0043] Preparation method, step 1: add them to the ball mill respectively, add appropriate amount of water, and ball mill together, the mass ratio of raw materials, ball stones, and water is 1:2:0.5, the mass ratio of large ball stones, medium ball stones, and small ball stones in high-aluminum ball stones is 2:5.5:2.5, the ball milling time is 18h, and the glaze is passed through a 120-mesh sieve after the ball is removed to obtain a glaze slurry,

[0044] Step 2: Add water to the base glaze to adjust to 42 degrees Baume, add water to the top glaze to adjust to 56 degrees Baume, use the dipping method to attach the base glaze slurry to the body, dry at 55℃~70℃ for 1h~1.5h, after drying, use the spraying method to evenly attach the top glaze to the base glaze, dry for 0.5 hours, send the glaze body into the roller kiln for firing, the firing cycle is 750min, the highest actual temperature of the kiln is 1280℃, and the firing curve is as follows Figure 1 As shown, the firing atmosphere is an oxidizing atmosphere.

[0045] The final glaze effect of the product is as follows Figure 3 shown.

[0046] A reaction glaze prepared by a preparation method of a cell-like structure reaction glaze provided by Example 2 has rich glaze reaction effects, obvious and moderate cell-like structure effects, good glaze gloss, various physical and chemical properties meet relevant national standards, and have good decorative effects.

[0047] Example 3

[0048] The present invention provides an embodiment, a cell-like structure reaction glaze, comprising the following raw materials in parts by weight:

[0049] Base glaze: 22 parts of frit, 28 parts of potassium feldspar powder, 14 parts of microcrystalline stone, 14 parts of wollastonite powder, 2 parts of calcined talc, 5 parts of molecular sieve, 3 parts of zinc oxide, 3 parts of Guizhou soil, 8 parts of 350 glaze powder;

[0050] Top glaze: 22 parts of frit, 28 parts of potassium feldspar powder, 14 parts of microcrystalline stone, 14 parts of wollastonite powder, 2 parts of calcined talc, 5 parts of molecular sieve, 3 parts of zinc oxide, 3 parts of Guizhou soil, 8 parts of 350 glaze powder, 5 parts of colorant, and 0.5 parts of high cobalt black.

[0051] Preparation method, step 1: add them to the ball mill respectively, add appropriate amount of water, and ball mill together. The mass ratio of raw materials, ball stone, and water is 1:2:0.5, and the mass ratio of large ball stone, medium ball stone, and small ball stone in high-aluminum ball stone is 2:5.5:2.5. The ball milling time is 18 hours. After the glaze is out of the ball, it is passed through a 120-mesh screen to obtain a glaze slurry;

[0052] Step 2: Add water to the base glaze to adjust to 42 degrees Baume, add water to the top glaze to adjust to 56 degrees Baume, use the dipping method to attach the base glaze slurry to the body, dry at 55℃~70℃ for 1h~1.5h, after drying, use the spraying method to evenly attach the top glaze to the base glaze, dry for 0.5 hours, send the glaze body into the roller kiln for firing, the firing cycle is 750min, the highest actual temperature of the kiln is 1280℃, and the firing curve is as follows Figure 1 As shown, the firing atmosphere is an oxidizing atmosphere.

[0053] The final glaze effect of the product is as follows Figure 4 shown.

[0054] A reaction glaze prepared by a method for preparing a cell-like structure reaction glaze is provided in Example 3. The reaction effect of the glaze surface is rich, and various physical and chemical properties meet the relevant national standards. The size of the crystals formed by crystallization is not uniform, and there are some glaze bubbles.

[0055] Comparative Example 1

[0056] The present invention provides a comparative example, comprising the following raw materials in parts by weight:

[0057] Base glaze: 18 parts of low-temperature frit, 20 parts of potassium feldspar powder, 18 parts of quartz powder, 10 parts of calcite powder, 3 parts of calcined talc powder, 3 parts of wollastonite powder, 5 parts of barium carbonate, 12 parts of zinc oxide, 6 parts of Longyan soil, 5 parts of zirconium silicate;

[0058] Glaze: 25 parts of low-temperature frit, 20 parts of albite powder, 15 parts of quartz powder, 12 parts of calcite powder, 3 parts of dolomite powder, 5 parts of barium carbonate, 10 parts of zinc oxide, 5 parts of Longyan soil, 5 parts of zirconium silicate, 3.5 parts of silver gray, 1 part of vanadium blue, 0.5 parts of brilliant black;

[0059] Preparation method, step 1: add them to the ball mill respectively, add appropriate amount of water, and ball mill together. The mass ratio of raw materials, ball stone, and water is 1:2:0.5, and the mass ratio of large ball stone, medium ball stone, and small ball stone in high-aluminum ball stone is 2:5.5:2.5. The ball milling time is 18 hours. After the glaze is balled, it is passed through a 120-mesh screen to obtain a glaze slurry. The bottom glaze is adjusted to 48 degrees Baume by adding water;

[0060] Step 2: Add water to the top glaze to adjust the temperature to 56 degrees Baume, and use the dipping method to attach the bottom glaze slurry to the body. Dry at 55℃~70℃ for 1h~1.5h. After drying, use the spraying method to evenly attach the top glaze to the bottom glaze. After drying for 0.5 hours, send the glaze body into the roller kiln for firing. The firing cycle is 340min, and the highest actual temperature of the kiln is 1190℃. The firing curve is as follows: Figure 1 As shown, the firing atmosphere is an oxidizing atmosphere.

[0061] The final glaze effect of the product is as follows Figure 5 shown.

[0062] The double-layer reaction glaze in Comparative Example 1 is an existing poor flow reaction glaze in Liling. From the analysis of the glaze effect, its reaction effect is vague, and various physical and chemical properties meet the relevant national standards. The flow effect is not obvious, the glaze surface is rigid, the reaction effect is uneven, and the reaction effect of the upper and lower layers is poor, which is not conducive to production. The chemical composition analysis of each raw material in the double-layer poor flow reaction glaze formula of the present invention is shown in Table 1:

[0063] Table 1 Chemical composition analysis of each raw material

[0064]

[0065] Frit: Produced in Liling, Hunan, it is the main flux in glaze. It has a strong fluxing effect, high gloss, and can increase the high-temperature fluidity of the glaze. However, its expansion coefficient is relatively large, so its usage in the glaze should be controlled reasonably.

[0066] Potassium feldspar powder: Produced in Rizhao City, Shandong Province, it is used as the main flux in glaze, which can reduce the melting temperature and viscosity of the glaze. Potassium feldspar has a wide melting temperature range and strong chemical stability, which is beneficial to controlling firing and preventing product deformation.

[0067] Microcrystalline stone: produced in Liling, Hunan.

[0068] Molecular sieve: produced in Liling, Hunan.

[0069] 350 glaze powder: produced in Liling, Hunan. Quartz is the main source of silicon dioxide in the glaze. Adding quartz to the glaze can improve the wear resistance, hardness, whiteness, transparency and chemical stability of the glaze.

[0070] Wollastonite: Produced in Shanggao, Jiangxi Province, its main components are silicon dioxide and calcium oxide, which can reduce the fluidity and elasticity of the glaze.

[0071] Calcined talc: produced in Shangrao, Jiangxi Province, its main component is MgO, which can reduce the melting temperature and expansion coefficient of the glaze and improve the elasticity of the glaze.

[0072] Zinc oxide: Produced in Shijiazhuang, Hebei, it is industrial zinc oxide that can act as a flux in the glaze, reduce expansion, prevent cracking, increase gloss and whiteness, have a favorable effect on elasticity, and expand the maturity temperature range.

[0073] Guizhou soil: Produced in Liling, Hunan, it introduces substances such as AL2O3 and SiO2 to make the glaze slurry suspended and stable, thereby increasing the melting temperature of the glaze.

Claims

1. A cell-like structure reactive enamel, characterized in that: The composition comprises the following raw materials in parts by weight: Base glaze: 21-23 parts of frit, 27-29 parts of potassium feldspar powder, 14-16 parts of microcrystalline stone, 13-16 parts of wollastonite powder, 1-3 parts of calcined talc, 4-6 parts of molecular sieve, 3-5 parts of zinc oxide, 2-4 parts of Guizhou soil, 6-8 parts of 350 glaze powder; Top glaze: 21 to 23 parts of frit, 27 to 29 parts of potassium feldspar powder, 14 to 16 parts of microcrystalline stone, 13 to 16 parts of wollastonite powder, 1 to 3 parts of calcined talc, 4 to 6 parts of molecular sieve, 3 to 5 parts of zinc oxide, 2 to 4 parts of Guizhou soil, 6 to 8 parts of 350 glaze powder, and 3 to 8 parts of colorant.

2. The cell-like structure reactive glaze according to claim 1, characterized in that: The raw materials include the following parts by weight: Base glaze: 22 parts of frit, 27 parts of potassium feldspar powder, 15 parts of microcrystalline stone, 14 parts of wollastonite powder, 2 parts of calcined talc powder, 4 parts of molecular sieve, 3 parts of zinc oxide, 3 parts of Guizhou soil, 7 parts of 350 glaze powder; Top glaze: 22 parts of frit, 27 parts of potassium feldspar powder, 15 parts of microcrystalline stone, 14 parts of wollastonite powder, 2 parts of calcined talc, 4 parts of molecular sieve, 3 parts of zinc oxide, 3 parts of Guizhou soil, 7 parts of 350 glaze powder, 5 parts of colorant, and 0.5 parts of high cobalt black.

3. The cell-like structure reactive glaze according to claim 1, characterized in that: The colorant used is ordinary light red tea colorant for ceramics.

4. A cell-like structure reaction glaze and a preparation method thereof, characterized in that The method comprises the following steps: Step 1: Weigh and mix the raw materials of base glaze and top glaze according to the weight ratio, and add appropriate amount of water; Step 2: wet ball milling, sieving, adjusting to a suitable concentration to obtain glaze slurry; Step 3: Then use the dipping method to attach the base glaze to the body, and then use the spraying method to evenly attach the surface glaze to the base glaze after drying. After drying again, it is sent to the tunnel kiln for firing. The maximum temperature is 1260℃~1290℃, the firing cycle is 13h~15h, and the firing atmosphere is an oxidizing atmosphere.

5. The cell-like structure reactive glaze and the preparation method thereof according to claim 4, characterized in that: The concentration of the base glaze slurry is controlled at 38 to 44 degrees Baume.

6. The cell-like structure reactive glaze and the preparation method thereof according to claim 4, characterized in that: The concentration of the top glaze slurry is controlled at 53-60 degrees Baume.

7. The cell-like structure reactive glaze and the preparation method thereof according to claim 4, characterized in that: After the glaze slurry is out of the ball, it is passed through a 160-mesh sieve and iron is removed with an iron removal rod.

8. The cell-like structure reactive glaze and the preparation method thereof according to claim 4, characterized in that: The base glaze is attached to the blank by the dipping method; the surface glaze is evenly attached to the base glaze by the spraying method.